2017
DOI: 10.5194/acp-17-1125-2017
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry–climate interactions of aerosol nitrate from lightning

Abstract: Abstract. Lightning represents one of the dominant emission sources for NO x in the troposphere. The direct release of oxidised nitrogen in the upper troposphere does not only affect ozone formation, but also chemical and microphysical properties of aerosol particles in this region. This study investigates the direct impact of LNO x emissions on uppertropospheric nitrate using a global chemistry climate model. The simulation results show a substantial influence of the lightning emissions on the mixing ratios o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 69 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…Using the GEOS-Chem model, Barret et al (2016) previously showed that Asian lightning NO x emissions make a major contribution to the photochemical ozone production within the ASM anticyclone. On the other hand, the direct impact of lightning NO x emissions on chemical and microphysical properties of global UT aerosols has recently received attention (Tost, 2017). Tost showed a major contribution from lightning NO x emissions to the UT nitrate aerosol burden in a global chemistry-climate model.…”
Section: Contribution Of Lightning No X To Nitrate In the Atalmentioning
confidence: 99%
“…Using the GEOS-Chem model, Barret et al (2016) previously showed that Asian lightning NO x emissions make a major contribution to the photochemical ozone production within the ASM anticyclone. On the other hand, the direct impact of lightning NO x emissions on chemical and microphysical properties of global UT aerosols has recently received attention (Tost, 2017). Tost showed a major contribution from lightning NO x emissions to the UT nitrate aerosol burden in a global chemistry-climate model.…”
Section: Contribution Of Lightning No X To Nitrate In the Atalmentioning
confidence: 99%
“…The uptake of SO 2 , HNO 3 , and NH 3 and the aqueousphase oxidation of SO 2 by H 2 O 2 and O 3 in clouds are calculated by the SCAV submodel (Tost et al, 2006a(Tost et al, , 2007a. The scavenging of gases and aerosols by wet deposition is calculated by the SCAV submodel (Tost et al, 2006a), and their removal through dry deposition is calculated by the DRY-DEP submodel . The SEDI submodel with a first-order trapezoid scheme is used to calculate the sedimentation of aerosols .…”
Section: Model Description and Setupmentioning
confidence: 99%
“…4 we will extend the comparison with various observations. Finally, physical loss processes, like dry deposition, wet deposition, and sedimentation of aerosol, are explicitly considered by the submodels DRYDEP, SEDI, and SCAV (Kerkweg et al, 2006;Tost et al, 2006a).…”
Section: Emac Modelmentioning
confidence: 99%